Neuronal networks in brain function, CNS disorders, and therapeutics - Faingold, Carl.; Blumenfeld, Hal.; ScienceDirect eBooks (London : Academic Press, 2014)
Neuronal Networks in Brain Function, CNS Disorders, and Therapeutics, edited by two leaders in the field, offers a current and complete review of what we know about neural networks. How the brain accomplishes many of its more complex tasks can only be understood via study of neuronal network control and network interactions. Large networks can undergo major functional changes, resulting in substantially different brain function and affecting everything from learning to the potential for epilepsy. With chapters authored by experts in each topic, this book advances the understa.
Selective Effects of CNS Drugs: Therapeutic Doses -- Drug Effects on Rhythmic Oscillations of the Brain -- Pharmacological Magnetic Resonance Imaging Studies -- Drug Effects on Intact Neuronal Networks -- Stimulant Drug Effects on Neuronal Network Neurons -- Stimulant Drug Effects and Cognition -- Depressant and Anesthetic Drug Effects on Neuronal Networks -- Effects of Ethanol on Neurons in Neuronal Networks -- Ethanol and Emergent Properties of Neurons -- Effects of Anticonvulsant Drugs on Intact Neuronal Networks for Seizures -- Anticonvulsant Actions on IC Neurons -- Anticonvulsant Actions on PAG and BRF Neurons -- Anticonvulsant Actions on the Substantia Nigra Reticulata (SNr) -- Emergent Properties: Differences between In vivo and In vitro Studies -- Understanding Emergent Properties as Critical Drug Targets -- "Anticonvulsant" Drug Effects on Networks for Multiple CNS Disorders -- CNS Drugs and Long-Lasting Network Changes -- Conclusion.
Print version record.
Includes bibliographical references and index.
Elsevier
Keywords: Neural networks (Neurobiology); Neuroanatomy; Nervous system -- Diseases; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Nervous system -- Diseases; Neural networks (Neurobiology); Neuroanatomy; Zentralnervensystem; Krankheit; Nervennetz; Neuroanatomie; Neurons; Brain; Central Nervous System Diseases; Nerve Net; Electronic books